Governance and Governed Multi-Country Perspectives on State, Society and Development (Springer Singapore, 2018)
Building, largely, on insights from India, and case studies in Brazil, China, and South Africa, this book provides insights into the contested topic of 'governance and governed' from a state-society inter-relationship perspective. It argues that the centrality of an understanding of state-governance today is rooted in concerns regarding diversities and contingencies of concrete political reality to address inequalities, exclusion and vulnerabilities. These countries are part of the BRICSs consortium, and have been recognised for their growth potential in the world economy. But their economic progress alone may not necessarily translate into a better quality of life. The approach here is not to focus on a particular understanding of governance, but to utilise a wider lens to understand the nature and extent of incremental processes in the different case-study contexts in order to offer a broader framework for procedural and substantive understanding of governance, rather than a prescription of a government and its activity of governing. The focus is on deriving practical lessons about governance process that are of interest to the wider development community.